Somatotypes of Javanese soccer and volleyball players in Yogyakarta - Neni Trilusiana Rahmawati, Neni Trilusiana Rahmawati (Universitas Gadjah Mada, 2003)
Background:There is considerable evidence indicating that athletes succeeding in certains sport have distinctive body types. Different body type patterns appear between sports and within sport, according to the demands of the sport and the competitive level.Objective: To study the somatotypes and to determine the specific morphological characteristics of soccer players and volleyball players compared to undergraduate male (non-athletes) in Yogyakarta. Method: 103 soccer and 73 volleyball players, and 48 non-athletes, aged 17 to 30 were recruited in the study. Sitting height, biacromial and bicristal breadth, stature, body weight, bicondylar breadths of humerus and femur, calf and upper arm circumferences, skinfolds at triceps, subscapular, calf, and supraspinal were obtained from each subject. Heath-Carter somatotypes were determined on the subjects. A one-way ANOVA, which used LSD (least significant differences) was employed to determine whether there were any statistically significant differences among 3 group means.Results: The results showed that the mean somatotype of soccer players were balanced mesomorph (2.6 - 4.9 - 2.9), volleyball players were mesomorph ectomorph (2.4 - 3.5 - 3.7), and non-athletes male were ecto-mesomorph (2.5 - 5.2 - 3.8Ã¯â¬Â´. The soccer players were significantly shorter, lighter, and more mesomorphic than the volleyball players. The volleyball players as a group tend to be taller and heavier than the soccer and the non-athletes.Conclusion: The findings indicated that the Yogyakarta soccer and volleyball players have similar somatotype distributions.Key words: somatotype - soccer players - volleyball players - Javanese - athletes